2016
DOI: 10.1038/srep23295
|View full text |Cite
|
Sign up to set email alerts
|

Room-temperature local ferromagnetism and its nanoscale expansion in the ferromagnetic semiconductor Ge1–xFex

Abstract: We investigate the local electronic structure and magnetic properties of the group-IV-based ferromagnetic semiconductor, Ge1−xFex (GeFe), using soft X-ray magnetic circular dichroism. Our results show that the doped Fe 3d electrons are strongly hybridized with the Ge 4p states, and have a large orbital magnetic moment relative to the spin magnetic moment; i.e., morb/mspin ≈ 0.1. We find that nanoscale local ferromagnetic regions, which are formed through ferromagnetic exchange interactions in the high-Fe-conte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

15
37
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(52 citation statements)
references
References 28 publications
15
37
0
Order By: Relevance
“…A significant difference between Ge:Fe and (Ga,Mn)As is that there is an additional Fe 3d electron in Ge:Fe which occupies the minority-spin 3d(e) states at the Fermi level. This means that Fe is in the Fe 2+ state with 3d 6 (sp) 2 configuration, consistent with the XAS and XMCD measurements [15] and a previous calculation on a 2 × 2 × 2…”
supporting
confidence: 75%
See 3 more Smart Citations
“…A significant difference between Ge:Fe and (Ga,Mn)As is that there is an additional Fe 3d electron in Ge:Fe which occupies the minority-spin 3d(e) states at the Fermi level. This means that Fe is in the Fe 2+ state with 3d 6 (sp) 2 configuration, consistent with the XAS and XMCD measurements [15] and a previous calculation on a 2 × 2 × 2…”
supporting
confidence: 75%
“…The present picture explains the observed increase of T C with Fe concentration [9] and with the inhomogeneity of Fe distribution [11]. The same picture explains the observation of nanoscale ferromagnetic domains formed in Fe-rich regions well above the T C [15].…”
supporting
confidence: 71%
See 2 more Smart Citations
“…According to their study, T C of Ge 0.895 Fe 0.105 is improved and reaches 210 K by the annealing below 600C, while the T C increases up to the room temperature when the annealing temperature is 600C; however, stacking fault and twins happen. They also investigated the local magnetic properties of (Ge,Fe) by the X-ray absorption spectroscopy (XAS) and soft X-ray magnetic circular dichroism (XMCD), and suggested that even at room temperature the local ferromagnetic region is still kept, and then the expansion of this region progress with decreasing temperature, resulting in the ferromagnetic phase transition 22 . For both the (Ge,Mn) and (Ge,Fe) cases, the inhomogeneous distributions of the Mn and Fe atoms plays an important role for the magnetic properties.…”
Section: Introductionmentioning
confidence: 99%